13.7-W 588-nm Yellow Laser Generation by Frequency Doubling of 885-nm Side-Pumped Nd: YAG-YVO4 Intracavity Raman Laser - Bing Sun; Xin Ding; Pengbo Jiang; Yuntao Bai; Xuanyi Yu; Yang Liu; Jingbo Wang; Lei Zhao; Tengteng Li; Guoxin Jiang; Peng Lei; Liang Wu; et al. (IEEE Photonics Journal, 2020)
An actively Q-switched all-solid-state YVO4 Raman laser, which used a 885-nm side-pumped Nd:YAG laser as the fundamental wavelength and delivered yellow output, is demonstrated. An in-band pump scheme is adopted to mitigate the thermal effects in the laser crystal and a Z-shaped laser cavity is used to compensate thermal lensing further. By intracavity frequency doubling of the Stokes wave with KTP crystal, 13.7-W yellow output at a wavelength of 588 nm, with a pulse repletion frequency of 10 kHz, was obtained under a diode pump power of 233 W. Additionally, single-pulse energy was 1.37 mJ with the pulse-width of 12.5 ns, corresponding to a peak power of 110 kW.